(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The article attempts to conduct a comparative analysis of modernization, globalization and globalism. It is proposed to distinguish between the concept of modernization in the broad and narrow, or special, senses. In the first sense, modernization is understood as constant evolution, constant renewal of the material and technical base of production, political structure, system of social relations, etc., which various societies go through in their history. Modernization in a special sense refers to the transformation of society that took place in Western Europe at the beginning of the New Age and continues to this day. The article supports the point of view according to which globalization and globalism are not the same thing. Globalization is understood as a gradual and steady interaction and convergence of various relatively isolated social formations into a single world human history. Modernization in a broad sense and globalization are only two sides of a single world-historical process. Globalism is the strategy and tactics of the leading capitalist countries, led by the United States, to manage the process of globalization in their own interests. To reveal the phenomenon of modernization and globalization, their comparative analysis, the following methods and principles were used: the principle of historicism, the principle of concreteness, comparative analysis, categories of essence and phenomenon, form and content. Key words: modernization in a broad sense, modernization in a special sense, globalization, globalism, world history, nation-state, world order, Western Europe.